2021
DOI: 10.4314/tfb.v29i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of cultured Clarias gariepinus and Tilapia zillii in Uyo, Akwa Ibom State, Nigeria

Abstract: The study examined helminth parasites of cultured Clarias gariepinus and Tilapia zillii in Uyo, Akwa Ibom State. A total of 60 fish samples (30 each of C.gariepinus and T. zillii) were subjected to parasitological examinations. Results revealed a total of 47(78.33%) fishes infected with various species of parasites: Nematodes (Camallanus polypteri, Paracamallanus cyathopharynx, and Procamallanus laevionchus), Cestodes (Polyonchobothrium torulosus and P. clariae) and Trematodes (Dactylogyrus extensus and Glossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The results of the present study revealed that microorganisms present in prawns include both bacteria and fungi species including: The microbial organisms isolated from the samples were Staphylococcus aureus, Enterobacter aerogenes, Bacillus cereus, Staphylococcus albus, Escherichia coli, Micrococcus sp., Atrobacter sp., Salmonella sp., Candida tropicalis, Aspergillus niger, Aspergillus flavus, Mucor mucedo, Rhizopus sp., and Aspergillus terreus. Reports had shown that infection rates of these microbial agent on organisms are a reflection of the general infestation from the habitats, inappropriate processing, preservation and storage condition (FDA, 2007;Ella et al, 2013;Bassey and Effiong, 2016;Effiong and Isaac, 2019;Effiong and Obot, 2020;Bubu-Davies et al, 2023). The reports of the present study agreed with the work of Srinivasan et al (2015) who recovered similar organisms from the gut of farmed giant freshwater prawn, Macrobrachium rosenbergii.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the present study revealed that microorganisms present in prawns include both bacteria and fungi species including: The microbial organisms isolated from the samples were Staphylococcus aureus, Enterobacter aerogenes, Bacillus cereus, Staphylococcus albus, Escherichia coli, Micrococcus sp., Atrobacter sp., Salmonella sp., Candida tropicalis, Aspergillus niger, Aspergillus flavus, Mucor mucedo, Rhizopus sp., and Aspergillus terreus. Reports had shown that infection rates of these microbial agent on organisms are a reflection of the general infestation from the habitats, inappropriate processing, preservation and storage condition (FDA, 2007;Ella et al, 2013;Bassey and Effiong, 2016;Effiong and Isaac, 2019;Effiong and Obot, 2020;Bubu-Davies et al, 2023). The reports of the present study agreed with the work of Srinivasan et al (2015) who recovered similar organisms from the gut of farmed giant freshwater prawn, Macrobrachium rosenbergii.…”
Section: Resultssupporting
confidence: 89%
“…The presence of Bacillus cereus, Micrococcus and Staphylococcus observed in the prawn samples was consistent with other studies (Effiong and Isaac, 2019;Effiong and Obot, 2020). It could be suggested that the presence of these organisms in prawn samples from these wetlands may be as a result of poor sanitary condition and improper handling of the samples by the fisher folks at the landing sites.…”
Section: Resultssupporting
confidence: 89%